Determinan Penerimaan Pengguna dan Kesiapan Organisasi Pada Implementasi Sistem Informasi Kesehatan Berbasis Model Utaut-Toe Scoping Review - Maulida Pramitasari; Silvia Kristanti Tri Febriana; Husaini Husaini; Izaak Zoelkarnain Akbar; Muhammad Abdan Shadiqi (Universitas Malahayati Lampung, 2025)
ABSTRACT Health Information Systems (HIS) play a crucial role in improving efficiency, service quality, and data-driven decision-making. However, their implementation still faces challenges such as low digital literacy and limited infrastructure. A deeper understanding of user acceptance and organizational readiness is essential for the success of digital transformation of health. This study aims to map the factors influencing user acceptance and organizational readiness in HIS implementation using the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Technology-Organization-Environment (TOE) frameworks, as well as to identify research gaps in previous studies. A scoping review method was conducted following the PRISMA-ScR guidelines. Literature searches were performed through PubMed, ScienceDirect, and Google Scholar databases using international keywords based on MeSH and Indonesian terms. Article selection followed the PCC (Population, Concept, Context) framework. Out of 4,469 identified articles, 30 studies met the inclusion criteria and were analyzed. The literature mapping revealed that within the UTAUT framework, key determinants of user acceptance included performance expectancy (18 studies), effort expectancy (18), social influence (19), facilitating conditions (18), and behavioral intentions (16). Within the TOE framework, important influencing factors included technological compatibility (7 studies), technological infrastructure (7), management support (8), and government policy (7). Most studies employed a quantitative cross-sectional design, while organizational culture, external environment, and longitudinal approaches were rarely explored. Successful HIS implementation requires a holistic approach integrating individual acceptance (UTAUT) with organizational readiness and environmental support (TOE). Further studies with longitudinal designs, multi-location contexts, and qualitative or mixed methods are needed to deepen the understanding of non-technical factors determining the success of health digitalization. Keywords: Health Information System, User Acceptance, Organizational Readiness, Unified Theory of Acceptance and Use of Technology (UTAUT), Technology-Organization-Environment (TOE) ABSTRAK Sistem Informasi Kesehatan (SIK) berperan penting dalam meningkatkan efisiensi, mutu layanan, dan pengambilan keputusan berbasis data. Namun, implementasinya masih menghadapi tantangan seperti rendahnya literasi digital dan keterbatasan infrastruktur. Perlu adanya pemahaman lebih lanjut terkait faktor penerimaan pengguna dan kesiapan organisasi sebagai kunci keberhasilan transformasi digital di bidang kesehatan. Penelitian ini bertujuan memetakan faktor penerimaan pengguna dan kesiapan organisasi dalam implementasi SIK menggunakan kerangka Unified Theory of Acceptance and Use of Technology (UTAUT) dan Technology-Organization-Environment (TOE), serta mengidentifikasi kesenjangan penelitian. Metode scoping review dilakukan dengan mengikuti pedoman PRISMA-ScR. Pencarian literatur dilakukan melalui basis data PubMed, ScienceDirect, dan Google Scholar dengan kata kunci internasional berbasis MeSH serta istilah dalam Bahasa Indonesia. Seleksi artikel mengacu pada kerangka PCC (Population, Concept, Context). Dari 4.469 artikel, 30 studi memenuhi kriteria dan dianalisis. Pemetaan literatur menunjukkan bahwa dalam kerangka UTAUT, determinan utama penerimaan pengguna meliputi performance expectancy (18 studi), effort expectancy (18), social influence (19), facilitating conditions (18), dan behavioral intentions (16). Dalam kerangka TOE, faktor penting yang berpengaruh meliputi kompatibilitas teknologi (7 studi), infrastruktur teknologi (7), dukungan manajemen (8), dan kebijakan pemerintah (7). Sebagian besar penelitian bersifat kuantitatif dengan desain cross-sectional, sementara dimensi budaya organisasi, lingkungan eksternal, serta pendekatan longitudinal masih jarang dieksplorasi. Keberhasilan implementasi SIK memerlukan pendekatan holistik yang mengintegrasikan penerimaan individu (UTAUT) dengan kesiapan organisasi dan dukungan lingkungan (TOE). Diperlukan penelitian lanjutan dengan desain longitudinal, konteks multilokasi, serta pendekatan kualitatif atau campuran untuk memperdalam pemahaman terhadap faktor nonteknis yang menentukan keberhasilan digitalisasi kesehatan. Kata Kunci: Sistem Informasi Kesehatan; Penerimaan Pengguna, Kesiapan Organisasi, UTAUT, TOE.